Analisa Faktor Pendorong dan Penarik Wisatawan Surabaya Dalam Memilih Vietnam Sebagai Pilihan Destinasi Wisatanya - Nerissa Aprilyani Limanto (Tourism Retailing+, 2013)
This study is acommplished to analyze which factors are push and pull, and which factors are dominant between push and pull factors Surabaya Tourists in choose Vietnam as a destination choice. The method for this research is descriptive research that attempted to describe phenomenon that exists with an accurate anlysis. Sample used in aged 24 – 65 years old who has an income and already had visited vietnam formerly in the last two years. Instrument used in this research is to use cross tab analysis and factors analysis. Based on the results of factor analysis it was known that the push factors to go on Surabaya tourist in choose Vietnam as a destination choice are Escape ,Relaxation and Prestige , Enhancement of Relationship and Wish Fulfillment. While the pull factors are: Affordable Price and Historical experiences, Beautiful Scenery, Cultural Show Attractions, Seeking of Activities, Accessibility. In overall, it can be concluded that Surabaya Tourist are more dominantly driven by push factor Escape ,Relaxation and Prestige and attracted by pull factor : Affordable Price and Historical experiences.